El derecho a la libertad y a la seguridad personales vulnerado por la ley 29569 - Aquino Santos, César Antonio (2012)
The present investigation has raised the problem of detention in criminal flagrancy developed by the Peruvian criminal procedural code and its collision with the right to freedom and personal security, so this investigation has been justified by establishing that the right to freedom is presented as A higher value of the legal order and has the category of fundamental right. Likewise, detention in cases of flagrant crimes constitutes a highly unique situation, with respect to the rule represented by the general respect and protection that for law to personal freedom, and the exception, constituted by detention by means of a written and duly substantiated judicial order. The present investigation has obtained theoretical and practical results, which show that paragraphs 3 and 4 of article one of the law 29569 that modifies Article 259 of the Code of Criminal Procedure if they violate the right to freedom and personal security prescribed in subsection 24 (f) of Article 2 of the Political Constitution of Peru. Since it is not in accordance with the guidelines of the Constitutional Court, it is contrary to the national and international doctrinal positions, the comparative legislation and the international treaties signed by the Peruvian state and the jurisprudence of the Inter-American Court of Human Rights. Must amend the law 29569, said amendment must incorporate the conceptual definition of flagrancy and delimit the essential requirements according to national and international jurisprudence and doctrine. In that sense the research has been proven and reaffirmed the hypothesis of the problem raised